2013
DOI: 10.1167/iovs.12-10980
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome and Risk of Age-Related Cataract over Time: An Analysis of Interval-Censored Data Using a Random-Effects Model

Abstract: PURPOSE. To investigate whether the effect of metabolic syndrome (MetS) and its components on the incidence of different cataract subtypes (cortical, nuclear, and posterior subcapsular cataract [PSC]) change with time. METHODS.A prospective cohort of persons 49 years of age and older were followed over 10 years in the Blue Mountains Eye Study, west of Sydney, Australia. MetS components as defined by the International Diabetes Federation criteria were measured at baseline (1992)(1993)(1994), after 5 years (1997… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 35 publications
2
15
0
1
Order By: Relevance
“…The present study revealed signi cant associations between cataract prevalence serum glucose levels and hemoglobin A1c levels, which is consistent with previous ndings [33,34]. In particular, we observed linear associations between hemoglobin A1c and fasting serum glucose levels and the presence of cataracts using generalized linear models, which suggests high fasting glucose levels and diabetes are risk factors of cataract development.…”
Section: Discussionsupporting
confidence: 93%
“…The present study revealed signi cant associations between cataract prevalence serum glucose levels and hemoglobin A1c levels, which is consistent with previous ndings [33,34]. In particular, we observed linear associations between hemoglobin A1c and fasting serum glucose levels and the presence of cataracts using generalized linear models, which suggests high fasting glucose levels and diabetes are risk factors of cataract development.…”
Section: Discussionsupporting
confidence: 93%
“…45-49, 50-54, 55-59, 60-64, 65-69, 70-74, 75-79), smoking (never, past, current ≤10, >10 cigarettes/day), alcohol consumption (g/day in quartiles), steroid medication use (yes/no), vitamin supplement use (yes/no), educational level (<10, 10-12, >12 years), physical activity (metabolic equivalent of the task, hr/day in quartiles). extraction is consistent with findings from cohort (Klein et al 1998;Jacques et al 2003;Lindblad et al 2008;Tan et al 2008;Ghaem Maralani et al 2013), cross-sectional (Leske et al 1999;Sabanayagam et al 2011;Richter et al 2012;Park et al 2014) and case-control studies (Galeone et al 2010). Glucose uptake in the lens is an insulin-independent process.…”
Section: Discussionsupporting
confidence: 88%
“…Only three prospective studies have examined the association between METS and cataract and/or cataract extraction (Lindblad et al 2008;Tan et al 2008;Ghaem Maralani et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…11 Yüksek kan glukozu ve beden kitle indeksinin beş yıllık izlemde kortikal katarakt; hem beş hem 10 yıllık izlemde ise arka subkapsüler katarakt riskini artırdığını, düşük HDL düzeyinin ise 10 yıllık izlemde artmış kortikal katarakt insidansı ile ilişkili olduğunu göstermişlerdir. 11 Tan ve ark., 10 yıllık izlemde, diyabetin yaşa bağlı katarakt için risk faktörü olduğunu, yeni tanı diyabette arka subkapsüler katarakt riskinin arttığını ve bozulmuş açlık glukozunun da kortikal katarakt için muhtemel bir risk faktörü olduğunu belirtmişlerdir. 12 Yüksek MetS indeksinin kortikal katarakt ile anlamlı ilişkisi olduğunu, obezitenin nükleer katarakt riskini artırdığını göstermişlerdir.…”
Section: öN Segment Hastaliklariunclassified